Cerebrospinal fluid electrolytes and acid-base in diabetic patients - Liao Chia-Chih (De Gruyter, 2021)
Diabetes mellitus (DM) has detrimental effects on the function of microvascular beds, resulting in blood–brain barrier (BBB) dysfunction. The objective of the study was to investigate whether DM affects the brain physiology through composition of cerebrospinal fluid (CSF) and compare gas tension and electrolyte levels in CSF between the diabetic and nondiabetic populations.